Design of a Web-Based IELP Test Result Inventory Application for IELP Raters at Palembang Aviation Polytechnic - Bintang Arif Manullang; Imam Sonhaji; Surya Tri Saputra (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
Air Traffic Controllers (ATCs) bear critical responsibility for ensuring aviation safety, efficiency, and orderly air traffic operations. One essential competency required of ATCs is English communication proficiency in accordance with the International Civil Aviation Organization (ICAO) English Language Proficiency (IELP) standard, with a minimum requirement of Level 4. At Palembang Aviation Polytechnic, IELP test result management is still conducted manually, relying on written documents and audio recordings stored on personal devices, which poses risks of data loss, duplication, and limited accessibility. This study aims to design a web-based application for the inventory management of IELP test results as a digital solution to support centralized, secure, and easily accessible data management for IELP raters. The research employed a Research and Development (R&D) approach using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. Data were collected through observation, interviews, expert validation, and user evaluation.